2019
DOI: 10.1029/2019ja026588
|View full text |Cite
|
Sign up to set email alerts
|

Currents Associated With Saturn's Intra‐D Ring Azimuthal Field Perturbations

Abstract: During the final 22 full revolutions of the Cassini mission in 2017, the spacecraft passed at periapsis near the noon meridian through the gap between the inner edge of Saturn's D ring and the denser layers of the planet's atmosphere, revealing the presence of an unanticipated low‐latitude current system via the associated azimuthal perturbation field peaking typically at ~10–30 nT. Assuming approximate axisymmetry, here we use the field data to calculate the associated horizontal meridional currents flowing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 20 publications
(64 reference statements)
3
17
0
Order By: Relevance
“…However, the inbound and outbound ΔΩ′ profiles presented in Figures 4a−4c are largely nonconjugate, which is mainly due to the polynomial subtraction process outlined in Section 1.1, where the detrended B ϕ profiles presented in Figure 2c show some asymmetries between the inbound and outbound passes for each Rev. If such asymmetries are physical, the nonconjugacy could indicate that the Pedersen conductances or angular velocity shears must either be spatially variable across ∼2 h of LT at the latitudes shown, or temporally variable on timescales longer than 10 min, which is consistent with results of Hunt et al (2019) who show that the ionospheric currents must be variable on the order of ≳30 min. The information presented in each panel is as follows: the angular velocity shears determined directly from the B ϕ observations, ΔΩ′ are presented by light green and dark green lines for the inbound and outbound legs of each Rev; black circle markers joined by a dashed black line show the * ΔΩ m values corresponding to the lowest RMSE * Ω m profiles from our modeling; the triangle markers show the local * Ω m values at the corresponding northern (blue) and southern (orange) latitudes; and the vertical bars associated the triangle markers show the range of Ω m values at the northern and southern latitudes from the wider range of models that fit the data well.…”
Section: Timeseries Of Angular Velocity Shears In Neutral Zonal Windssupporting
confidence: 82%
See 1 more Smart Citation
“…However, the inbound and outbound ΔΩ′ profiles presented in Figures 4a−4c are largely nonconjugate, which is mainly due to the polynomial subtraction process outlined in Section 1.1, where the detrended B ϕ profiles presented in Figure 2c show some asymmetries between the inbound and outbound passes for each Rev. If such asymmetries are physical, the nonconjugacy could indicate that the Pedersen conductances or angular velocity shears must either be spatially variable across ∼2 h of LT at the latitudes shown, or temporally variable on timescales longer than 10 min, which is consistent with results of Hunt et al (2019) who show that the ionospheric currents must be variable on the order of ≳30 min. The information presented in each panel is as follows: the angular velocity shears determined directly from the B ϕ observations, ΔΩ′ are presented by light green and dark green lines for the inbound and outbound legs of each Rev; black circle markers joined by a dashed black line show the * ΔΩ m values corresponding to the lowest RMSE * Ω m profiles from our modeling; the triangle markers show the local * Ω m values at the corresponding northern (blue) and southern (orange) latitudes; and the vertical bars associated the triangle markers show the range of Ω m values at the northern and southern latitudes from the wider range of models that fit the data well.…”
Section: Timeseries Of Angular Velocity Shears In Neutral Zonal Windssupporting
confidence: 82%
“…Hunt et al. (2019) calculate the intra D‐ring field‐aligned currents from the B ϕ measurements during the Grand Finale orbits, and show that the large scale structure of the currents appear to be in steady state (on timescales < 30 min) between the inbound and outbound legs of each Rev, but are variable from orbit to orbit. They also find that the small scale structure in the currents does not show the same level of conjugacy between the inbound and outbound legs of each Rev.…”
Section: Modeling the Temporal Variability In The Azimuthal Magnetic mentioning
confidence: 99%
“…Fig. 3B shows the measured azimuthal component, B φ , along Rev 291 which remains within ± 50 nT and exhibits various magnetospheric features including the auroral FACs (Hunt et al 2014(Hunt et al , 2015(Hunt et al , 2018, low-latitude (intra-D ring) FACs Khurana et al 2018;Provan et al 2019a;Hunt et al 2019), crossing of the Enceladus fluxtube (Sulaiman et al 2018), and PPOs (Provan et al 2019b). Fig.…”
Section: Introductionmentioning
confidence: 93%
“…The peak field strength is not encountered at the periapsis but at mid-latitude in the southern hemisphere. The overall features of the measured magnetic field are highly repeatable from orbit to orbit, although the magnetospheric features such as auroral FACs and intra-D ring FACs do exhibit orbit to orbit variations (Provan et al 2019a;Hunt et al 2019).…”
Section: Introductionmentioning
confidence: 95%
“…They showed that to explain the planetary magnetic field at periapsis, an axisymmetric 11‐degree spherical harmonic model was required and that Saturn's dipole axis tilt must be less the 0.007° from the spin axis of the planet. In addition, a field‐aligned current system was discovered to flow along field lines that thread the region inside the D‐ring, Saturn's innermost ring (Dougherty et al, 2018; Hunt et al, 2019; Khurana et al, 2018; Provan et al, 2019). Recently, Provan et al (2019) determined the PPO and mean residual field on the Proximal orbits from the auroral region to the gap between Saturn and the D‐ring by performing sinusoidal fits to the data in bins of colatitude.…”
Section: Introductionmentioning
confidence: 99%